Accounting and accountability in the Anthropocene. Issue 1 (12th November 2019) - Bebbington, Jan; Österblom, Henrik; Crona, Beatrice; Jouffray, Jean-Baptiste; Larrinaga, Carlos; Russell, Shona; Scholtens, Bert
Abstract : Purpose: The purpose of this paper is to interrogate the nature and relevance of debates around the existence of, and ramifications arising from, the Anthropocene for accounting scholarship. Design/methodology/approach: The paper's aim is achieved through an in-depth analysis of the Anthropocene, paying attention to cross-disciplinary contributions, interpretations and contestations. Possible points of connection between the Anthropocene and accounting scholarship are then proposed and illuminated through a case study drawn from the seafood sector. Findings: This paper develops findings in two areas. First, possible pathways for further development of how accounting scholarship might evolve by the provocation that thinking about the Anthropocene is outlined. Second, and through engagement with the case study, the authors highlight that the concept of stewardship may re-emerge in discussions about accountability in the Anthropocene. Research limitations/implications: The paper argues that accounting scholarship focused on social, environmental and sustainability concerns may be further developed by engagement with Anthropocene debates. Practical implications: While accounting practice might have to change to deal with Anthropocene induced effects, this paper focuses on implications for accounting scholarship. Social implications: Human well-being is likely to be impacted if environmental impacts accelerate. In addition, an Anthropocene framing alters the understanding of nature–human interactions and how this affects accounting thought. Originality/value: This is the first paper in accounting to seek to establish connections between accounting, accountability and the Anthropocene.